Investigating the security consequences of climate change on Iran with a Good Governance approach - Parisa ghorbani sepehr; Zaki Yashar; Seyed abbas ahmadi (تحقیقات کاربردی علوم جغرافیایی)
Due to its location in low latitudes, Iran is among the countries that has not been spared from the security consequences of climate change. The present study seeks to answer two questions: 1) What are the security consequences of climate change on Iran and which components have the greatest impact on Iran? 2) Which of the pillars of good governance as a solution has the greatest impact on reducing the effects of climate change on Iran? In this study, the study population is elites and experts familiar with the subject of the study, 100 of whom were selected for snowball sampling and a researcher-developed questionnaire was used to collect data. Data were evaluated using SPSS and MINITAB software. The results of the studies according to the obtained P-value which is equal to 0.000 and is less than 0.05 alpha, indicate the difference between the natural and human consequences of climate change in Iran. The results of the Tukey test indicate that the natural consequences of climate change with an average of 4.0584 are in group A and the human consequences with an average of 3.4460 are in group B. Also, the results of Friedman test on the effect of good governance in controlling and reducing the security consequences of climate change in Iran show that accountability with an average of 5.79 in the first place, rule of law with an average of 5.62 in the second place. and accountability of officials with an average rating of 5.32 are in third place.